2007
DOI: 10.1172/jci30111
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation, atrophy, and gastric cancer

Abstract: The association between chronic inflammation and cancer is now well established. This association has recently received renewed interest with the recognition that microbial pathogens can be responsible for the chronic inflammation observed in many cancers, particularly those originating in the gastrointestinal system. A prime example is Helicobacter pylori, which infects 50% of the world's population and is now known to be responsible for inducing chronic gastric inflammation that progresses to atrophy, metapl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

17
626
0
16

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 691 publications
(671 citation statements)
references
References 120 publications
17
626
0
16
Order By: Relevance
“…The association between inflammation and cancer is well established, and in particular GC is a prime example, in which HP infection induces chronic gastric inflammation that progresses to atrophy, metaplasia, dysplasia, and malignancy (Fox et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The association between inflammation and cancer is well established, and in particular GC is a prime example, in which HP infection induces chronic gastric inflammation that progresses to atrophy, metaplasia, dysplasia, and malignancy (Fox et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…1,2 HP-infected gastric mucosa progresses through stages of chronic gastritis, glandular atrophy, intestinal metaplasia, dysplasia, and gastric cancer. 3 HP produce a variety of virulence factors such as CagA and VacA that can affect host intracellular signaling pathways and play an important role in determining the outcome of HP infection. 3 However, they are not absolute determinants of clinical outcomes because most individuals remain asymptomatic after HP infection.…”
mentioning
confidence: 99%
“…3 HP produce a variety of virulence factors such as CagA and VacA that can affect host intracellular signaling pathways and play an important role in determining the outcome of HP infection. 3 However, they are not absolute determinants of clinical outcomes because most individuals remain asymptomatic after HP infection. 4 The variable outcomes of HP infection can be attributed to inflammatory responses governed by host factors as well as HP virulence factors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is suggested that increased cell proliferation in gastric epithelium in vivo might be an indirect or secondary response to H. pylori infection [43][44][45]. Together with the previous publications that suppressed apoptosis might be one of major pathogenic factors in H. pylori-associated carcinogenesis [46][47][48] and oncogenic stem cells contributed to H. pylori-associated carcinogenesis [49], we could conclude that the reemergence of Shh expressing cells can explain these compensatory or counteractive privileges of proliferation through imbalanced epithelial turnover and this anti-apoptotic steps and proliferative privileges through Shh reactivation could be the necessary path for H. pylori-associated carcinogenesis. Even though we found the possible role of switching expression of Shh during the progression of gastric diseases after H. pylori infection, more documentation to define the role of Shh expression in H. pylori gastric carcinogenesis, especially progression from adenoma to carcinoma will be required to draw the definite conclusion.…”
Section: Discussionmentioning
confidence: 74%